Bempedoic Acid: A Novel Approach in Managing Dyslipidemia and Reducing Cardiovascular Risk - Łukasz Wołowiec; Małgorzata Pellowska; Michał Janiak; Lidia Wydeheft; Grzegorz Grześk; Walery Zukow (Kazimierz Wielki University, 2024)
Cardiovascular disease remains one of the leading causes of mortality worldwide, with elevated LDL cholesterol being a critical risk factor. Statins have long been the cornerstone of lipid-lowering therapy, but many patients fail to reach target LDL cholesterol levels due to statin intolerance or insufficient response, even when combined with ezetimibe. Recently, the lipid-lowering drug class has been expanded with the introduction of bempedoic acid, a novel agent that inhibits ATP-citrate lyase. Recent studies have demonstrated the efficacy and safety of bempedoic acid in reducing LDL cholesterol levels in patients with hypercholesterolemia, paving the way for its inclusion in clinical guidelines. This article provides a comprehensive overview of the latest evidence regarding bempedoic acid and its emerging role in lipid management. Despite the widespread use of statins, many patients fail to achieve target LDL-C levels due to statin intolerance or insufficient response. This comprehensive review explores the emerging role of bempedoic acid, a novel lipid-lowering agent that inhibits ATP-citrate lyase, in the management of dyslipidemia and cardiovascular risk reduction. Bempedoic acid, approved by the FDA in 2020, offers a unique mechanism of action that complements existing therapies. As a prodrug activated specifically in the liver, it avoids muscle-related side effects commonly associated with statins. Clinical trials have demonstrated its efficacy in reducing LDL-C levels, particularly in patients with statin intolerance or those requiring additional LDL-C lowering beyond maximally tolerated statin therapy. The review synthesizes data from multiple phase 3 clinical trials, including CLEAR Wisdom and CLEAR Outcomes, which have shown significant LDL-C reductions with bempedoic acid monotherapy and in combination with other lipid-lowering agents. Notably, bempedoic acid not only lowers LDL-C but also reduces high-sensitivity C-reactive protein (hs-CRP) levels, suggesting potential anti-inflammatory effects. Safety profiles from these trials indicate that bempedoic acid is generally well-tolerated, with minimal muscle-related adverse events. However, slight increases in serum creatinine and uric acid levels have been observed, warranting monitoring in certain patient populations. Recent updates to clinical guidelines, including the 2024 European Society of Cardiology guidelines on coronary heart disease, now recommend bempedoic acid for specific patient groups. These include statin-intolerant patients not achieving LDL-C goals on ezetimibe alone, and those not reaching targets on maximum tolerated statin doses combined with ezetimibe. This review concludes that bempedoic acid represents a significant advancement in lipid-lowering therapy, offering a valuable option for patients with hypercholesterolemia, particularly those with statin intolerance or requiring additional LDL-C reduction. As research continues, bempedoic acid's role in reducing cardiovascular events and its long-term safety profile will be further elucidated, potentially reshaping the landscape of dyslipidemia management and cardiovascular risk reduction.